Objectification of Women in Alhamad’s Novels: A Question of De-Humanization or Empowerment in a Post-Islamic Awakening Narrative - Alazaz, Hanan Abdulaziz (International Journal of Language and Literary Studies, 2024)
This paper reviews the work of the Saudi novelist, Turki Alhamad, who published in a post-Islamic Awakening in Saudi Arabia. The paper contextualizes his writing by defining the concept of sexual objectification in various theorizations of the term including several texts that represent the discourse of the Islamic Awakening movement. His work can be perceived to be de-humanizing of women particularly during the time of its publication in the 1990s and early 2000s when the movement was popular. However, a close reading of his work suggests a multiplicity of discourses in his representation of women. His work can be empowering women taking into consideration Alhamad’s non-fictional writings that promote social change in Arab and Muslim countries. Branded as a challenge of social values at the time of its publication, his work can also be interpreted as a precursor to the social shift towards women’s empowerment that took place in Saudi Arabia in recent years.